The Liar - Kaurismäki, Mika; Gauditz, Kay; Sulzbeck, Toni; Varja, Olli; Kaurismäki, Aki; Hämäläinen, Pirkko; Hirvikangas, Juuso (Bluebell Films, 2008)
In "The Liar" (Valehtelija) Ville Alfa (Aki Kaurismäki), an overly intellectual, amoral, manic young wastrel, cannot stop telling lies. His dishonesty enables him to seduce girls and borrow money from friends, family and total strangers but he abandons people the minute the going gets tough, or if it suits him, or if he thinks the grass is greener elsewhere. Finally his compulsive lies land him in hot water ... The camerawork, in black and white, gives the film a certain edge and the Kaurismäki's performance, which really brings this repugnant character to life ... [www.eyeforfilm.co.uk]
Keywords: DVD-Video